Is there an optimal size for the financial sector? - Santomero, Anthony M.; Seater, John J. (Journal of Banking & Finance, 2000)
This paper derives the optimal size of the financial sector using a general equilibrium framework that is an extension of the paper of Holmstrom and Tirole (1997) [Quarterly Journal of Economics 112, 663–691]. We show that the financial sector has a unique optimal size relative to the size of the economy as a whole. Creating and maintaining this sector requires diversion of some physical capital from production of output to monitoring that production. However, the efficiency gain in output production brought about by monitoring warrants the diversion. It is also found that the optimal size of the financial sector is independent of the state of the economy and does not vary over the business cycle.